Definitive salvage chemotherapy for the treatment of refractory/relapsed non-Hodgkin lymphoma, a single center experience. Issue 4 (1st December 2018) - Hafez, Rania; Hussein, Safinaz; Ismail, Marwa
Abstract: Objective: Non Hodgkin Lymphomas (NHL)s are a group of malignancies which affect the lymphatic system. A significant proportion of NHL patients experience either relapse or failure of treatment which is called refractory disease. Relapsed or refractory NHL usually have poor prognosis due to shortage of randomized trials comparing efficacy of different treatment protocols to define the optimal salvage chemotherapy regimen in these cases. In this study, we are trying to define the best salvage chemotherapy regimen with low toxicity and better quality of life for patients by comparing outcome of 2 salvage chemotherapy regimens GDP & DHAP. Patients and methods: 100 patients diagnosed as relapsed or refractory NHL were randomly assigned to receive either Gemcitabine, Dexamethasone and Cisplatin (GDP) or Dexamethasone, Cytarabine and Cysplatin (DHAP) for 4 to 6 cycles. Primary endpoints of the study were overall survival and progression free survival. Secondary endpoints were response to treatment, toxicity profile of each regimen, and quality of life assessment. Results: The overall response rate was 70% in GDP group & 64% in DHAP group with no statistically significant difference between them (p-value 0.5). There was no significant difference between both groups regarding toxicity profile except in febrile neutropenia episodes which was much less in GDP group (p-value 0.04). Quality of life was better in GDP group than DHAP with significant difference (p-value < 0.05). There was no statistical significant difference between both groups regarding OS or PFS. Conclusion: GDP is as effective as DHAP for relapsed or refractory lymphoma with less toxicity and better quality of life.